2021
DOI: 10.1186/s12879-021-06785-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus seasonality, respiratory infections and weather

Abstract: Background The survival of coronaviruses are influenced by weather conditions and seasonal coronaviruses are more common in winter months. We examine the seasonality of respiratory infections in England and Wales and the associations between weather parameters and seasonal coronavirus cases. Methods Respiratory virus disease data for England and Wales between 1989 and 2019 was extracted from the Second-Generation Surveillance System (SGSS) database… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 90 publications
1
49
0
1
Order By: Relevance
“…Studies conducted in China [ 49 , 91 ] and Indonesia [ 44 ] also found that high temperature and humidity were associated with lower rates of COVID-19. Meanwhile, an ongoing study of viral infections in England by Nichols et al [ 92 ] revealed that transmissibility of coronavirus depends on season, reaching a peak in winter (daily mean temperature below 10 °C, sunshine of less than 5 h/day and relative humidity over 84%), which implies a seasonal increase for COVID-19 infections in countries experiencing similar climate. A study conducted by Christophi et al [ 78 ] reported a 10 °C rise in ambient temperature resulted in 6% lower COVID-19 mortality rates at 30 days after the first reported death in Organization for Economic Co-operation and Development (OECD) countries and the United States.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in China [ 49 , 91 ] and Indonesia [ 44 ] also found that high temperature and humidity were associated with lower rates of COVID-19. Meanwhile, an ongoing study of viral infections in England by Nichols et al [ 92 ] revealed that transmissibility of coronavirus depends on season, reaching a peak in winter (daily mean temperature below 10 °C, sunshine of less than 5 h/day and relative humidity over 84%), which implies a seasonal increase for COVID-19 infections in countries experiencing similar climate. A study conducted by Christophi et al [ 78 ] reported a 10 °C rise in ambient temperature resulted in 6% lower COVID-19 mortality rates at 30 days after the first reported death in Organization for Economic Co-operation and Development (OECD) countries and the United States.…”
Section: Resultsmentioning
confidence: 99%
“…A positive relationship between long-term PM 2.5 exposure and COVID-19 cases, hospital admissions and deaths has been reported by Mehmood et al, [ 100 ] and Cole et al [ 32 ], in India, Pakistan, and Iraq. A strong association between PM 2.5 and PM 10 and COVID-19 case fatality rates (CFR) was found in 49 Chinese cities, including Wuhan, the epicenter of the COVID quake [ 92 ]. Yao et al [ 93 ] found that over 45 days, for every 10 μg/m 3 increase in PM 2.5 and PM 10 concentrations, COVID-19 CFR increased by 0.24% and 0.26%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The LumiraDx SARS-CoV-2 and Flu A/B Test can potentially allow healthcare professionals to quickly and specifically identify the infection and decide on appropriate containment and treatment strategies. Multiplex testing for respiratory infections in point-of-care settings is essential as seasonal influenza and COVID-19 outbreaks may become the new normal [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In temperate climate regions viral respiratory infections are known to have higher incidence during the winter, and earlier studies have shown that ambient temperature and humidity play a role in the seasonal nature of respiratory viral infection outbreaks [ 1 , 2 , 3 ]. Data from England and Wales show that coronaviruses predating SARS-CoV-2 had a similar seasonal distribution as influenza A and bocavirus during 2012–2019 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Meteorological Organization (WMO) [ 5 ] divided the mechanisms of how meteorological factors can influence transmission into virus viability, host immunity and human behavior. Nichols et al [ 4 ] divided the drivers of seasonal infection dynamics into immunological, weather-related, social, and travel-related factors. Studies on virus survival rates have shown that prolonged virus viability and transmissibility are associated with cooler and drier low-humidity environments as these conditions favor rapid evaporation of water from exhaled aerosols [ 2 , 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%